(untitled) (Global Media Journal - German Edition, 2018)
Formal journalism education in Ukraine has been criticized for quite a long time for still being affected by the old Soviet theory-based teaching model, rather than adhering to internationally accepted best practices. The system of teaching students at journalism departments has not changed significantly since Ukrainian independence in 1991 and many Ukrainian journalists have entered the profession with largely inadequate training. For instance, the practice of on-the-job training has been implemented only by some journalism departments, or is partly implemented by some lecturers. On the other hand, graduates of journalism programs in Ukraine say that more practical trainings help their professional growth. This article, then, aims to explicate the advantages and disadvantages that exist in Ukrainian journalism education, and it seeks to reveal whether Ukrainian journalists prefer formal or non-formal education for their profession. The findings are based on an analysis of 10 focus groups conducted with a total of 92 Ukrainian journalists (both with and without journalism degrees) and nine in-depth interviews with Ukrainian lecturers and Ukrainian media representatives.